Mineral trioxide aggregate but not light-cure mineral trioxide aggregate stimulated mineralization - Gomes Filho, João Eduardo [UNESP]; Faria, Max Dougals de [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP]; Costa, Mariana Macbado Teixeira de Moraes [UNESP]; Cannon, Mark (Elsevier B.V., 2008)
The purpose of this study was to evaluate the subcutaneous response of rat connective tissue to light-cure MTA and Angelus MTA. These materials were placed in polyethylene and dentin tubes and implanted into dorsal connective tissue of Wistar rats for 30 and 60 days. The specimens were prepared to be stained with hematoxylin-eosin, Von Kossa, and without stain for polarized light and evaluated in an optic microscope. The Angelus MTA showed a mild inflammatory response at 30 days and none at 60 days, characterized by organized connective tissue, presence of some chronic inflammatory cells, and induction of mineralized tissue formation. Light-cure MTA presented a moderate chronic inflammatory response at 30 days that decreased at 60 days but was more intense than with Angelus MTA and without dystrophic calcifications. It was possible to conclude that light-cure MTA was similar to MTA at 60 days, but it did not stimulate mineralization.
Keywords: biocompatibility; MTA; subcutaneous connective tissue